Crystal chemical adaptations of the apatite structure for the incorporation of simulated high level nuclear waste (HLW) - Lim, Sing Chin (2012)
Singapore has achieved outstanding econmic success since gaining independence, through the creation of industrial pillars in finance, shipping, semiconductors, petrochemicals, and more recently, biotechnology. These activities consume considerable raw materials and such progress is all the more remarkable in a city-state entirely dependent on important of resources. The econmy is also energy intensive, and to date, Singapore has relied primarily on oil-fired electrical power stations to meet its needs. However, in an uncertain world, diversification of energy supply is prudent, and for this reason Singapore is considering the nuclear power option.